(untitled) (Kronika Bydgoska, 2010)
Nowadays cars play an important role in the lite of each big city. Were they eąually important in the city on the Brda River in the 20-year inter-war period? The number of cars registered at that time in Bydgoszcz was not too high, and thus there was no traffic jam problem, but on the other hand the statistics showed only backwardness in this field. This article presents motorisation in Bydgoszcz at that time, showing the ways of usage of cars for financial purposes and how motor vehicles served the residents’ practical and entertainment needs.